Relation through co-creation: Research on co-creation in the transnational CoTalent project based on network theory - Etienne Koot (Journal of the European Honors Council)
The CoTalent project is a unique collaboration between eight universities (of applied sciences) throughout Europe funded by the Erasmus+ program of the European Commission. The objective of the CoTalent project was to use co-creation with teachers and students in order to create tools that would support higher education to foster and recognize talented students. Three toolsets were made with a total of around 920 students and teachers via workshop weeks and so-called multiplier event. This current research projects the impact of the student participants through a social network theory perspective to look at what the co-creation of the CoTalent project can do for them in their professional career (including their education). By conducting eight interviews with the student participants, it became clear the CoTalent network was a unique network that shares the characteristics of both strong- and weak ties. The members involved were of many cultures and origins but simultaneously of a similar mindset which made for a fertile network in terms of productivity to complete the tasks at hand and in terms of the student participant their experience. The participating students mainly experienced growth in soft skills and gained new perspectives through the diverse set of actors involved.